Management of Stahl’s ear: a case report - João Maximiliano; Antônio Carlos Pinto Oliveira; Leonardo Milanesi Possamai; João Bombardelli; Marcus Vinicius Martins Collares (Revista Brasileira de Cirurgia Plástica)
Stahl's ear deformity was first described in the 19th century and it consists of a rare auricular deformity characterized by hypoplasia of the antihelix crus with enlargement of its base and a third crus of the antihelix connected to posterior portion of helix crus, which deforms the posterolateral wall of the external auditory canal. Reconstructive surgery is the definitive treatment, however, because of the diversity of clinical presentations, no standard technique exist for all cases. The method described in this report is another treatment option and entails the resection of the third crus and reconstruction of superior crus of the antihelix.